Conservation of natural heritage in the Bursa Hanlar District: An investigation into monumental plane trees - Çelik, Seda Çil; Erken, Kamıl (My University, 2025)
Objective: This study aims to identify the difficulties and challenges faced by monumental trees in a historically protected area, compare their current and desired living conditions and develop solutions to the issues they experience. Material and Methods: The study assessed the current living conditions and physical state of the monumental plane trees. The differences were identified by comparing their current condition with their expected size and habitat to be protected. Monumental trees were examined in terms of trunk and crown health status, and solution proposals were developed for the identified problems. Results: The data revealed that 85% of the monumental trees were below the required height and diameter. None of the monumental trees in the study area had sufficient living space. Furthermore, 95% of the trees exhibited inadequate root areas, and their forms had deteriorated due to deep pruning; 90% showed signs of branch dieback, 70% had galls and swellings, 55% insufficient crown area, and 50% had cavities and rot in their trunks. Conclusion: To ensure the sustainability of the monumental trees in the study area, they must be protected according to the TS 13190 standard, with special care and rehabilitation measures implemented. Without these interventions, many of these monumental trees, which have already lost many characteristics, may disappear within a few decades.
Keywords: Sustainability; Maintenance; monumental trees; plant health